A community in transition : the Biharis in Bangladesh - Rahman, Mizanur 1956-; Empowerment Through Law of the Common People (Project) (Dhaka : Empowerment Through Law of the Common People, 2003)
Contributed articles; with reference to political and social history of Bihari (South Asian people) of Bangladesh.
Includes bibliographical references and index.
Keywords: Bihari (South Asian people) -- Bangladesh -- History; Bangladesh -- History